Insurance Protection in Risky Tourism Activities - Danendra Yusuf, Mohamad Zulfikar; Abdussamad, Zamroni; Rivadi Moha, Mohamad (Universitas Negeri Gorontalo, 2024)
Insurance protection in risky tourism activities is very important, especially in areas with high potential and risky natural tourism, such as South Bolaang Mongondow Regency. This research aims to analyze the role of insurance protection in reducing the risks faced by tourists and tourism managers in the area. Using a qualitative approach, this research examines the different types of insurance applied in the tourism industry, including health, accident and property damage insurance. It also discusses the factors that influence the application of insurance in the tourism sector, the challenges faced by stakeholders, and the importance of socialization and education on the benefits of insurance protection for tourists. The results show that although some tourism managers have implemented insurance for tourists, there are still gaps in understanding and optimal implementation of insurance in South Bolaang Mongondow Regency. Therefore, there is a need for increased awareness and collaboration between the government, tourism managers, and insurance companies to create a more effective and efficient protection system for risky tourism activities in the area